Associative Factors of Acculturative Stress in Latino Immigrants - Kedem, Sam (2015)
For the past 200 years, Latinos have comprised the largest, consistent category of immigrants in the United States. This influx has created a need for culturally competent psychological treatment of a population that suffers from acculturative stress, defined as the stress a minority member experiences while trying to adjust to the culture of the majority. Researchers have studied Latino immigrants' enduring trials as they adjust to life in the United States. Nevertheless, there is limited research on the quantification of factors contributing to acculturative stress. Based on the conceptual framework of bidimensional acculturation and Latina/o critical race theory, predictors of acculturative stress among Latino immigrants (N = 172) were examined in this quantitative cross-sectional study. Data were collected using a convenience sample from several public areas located in Miami, Florida. Forced entry regression analysis weighed factors such as: documentation status, experiencing prejudice, gender, income, the number of family members present, confidence in English, age, and number of years in the United States. The results demonstrated only experienced prejudice weighed significantly in the regression model (β = .43, p < .05), and was therefore correlated with acculturative stress scores. The results of this study may help to increase mental health professionals' awareness of how experiences of discrimination can impact the acculturative stress of their immigrant clients. To improve service to this community, mental health professionals and their institutions can take steps to counteract the biases associated with the acculturative stress of Latino immigrants, thereby establishing themselves as an ally to this population